Pengaruh Variasi Debit Udara Terhadap Efisiensi Penyisihan Cod Dalam Limbah Cair Hotel Pada Sistem Moving Bed Biofilm Reactor (MBBR) Menggunakan Chorella Sp. - Aulia Masta; Shinta Elystia; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Hotel wastewater contains pollutants such as COD if discharged directly the environment has a harmful effect on the environment. If not processed it will cause excessive growth of algae or aquatic plants (eutrophication). The study was conducted to determine the efficiency of waste treatment hotel in reducing the parameter of COD using the method Moving Bed Biofilm Reactor (MBBR) by utilizing Chorella sp. This research was carried out by growing biofilms on kaldness (K1) media and air injection by aerators with variations of air injection 3 L/minute ; 6 L/minute ;9 L/minute ; and control (without air injection) with processing time of 5 days. Based on the results of wastewater treatment research hotel with the MBBR method with air injection 6 L/minute, it was able to reduce the parameters of COD to below the quality standard. The highest cell density of Chorella sp. suspended and attached in a row that is 1,595 dan 1,587 (x107 cell/ml) with the density of the cell is able to reduce the COD parameter from concentration of 485,6 mg/L to 80 mg/L and efficiency of 83,53 %, so that hotel wastewater doesnot pollute the environment if it is discharged into water bodies.Keywords : COD, Kaldness (K1), Hotel Wastewater, MBBR, Chorella sp. Microalgae.